2021
DOI: 10.5198/jtlu.2021.1796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating demand responsive transit services using a density-based trip rate metric

Abstract: Demand responsive transit (DRT) is attracting increased attention as a means to provide public transit to low-density populations. This research aims to provide a suite of evaluation metrics with low data requirement and widespread availability, so that operators, funders, regulators, and practitioners can better evaluate the performance of DRT services. Trip numbers can be divided by a number of available variables (period, trip length, population, and density) to create a number of derived metrics. By applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Accordingly, Kaufman et al [33] found in his studies that car use was mainly explained by the local and sub-regional built environment (e.g., walkability, access to work by bus) rather than rail access and Efforts to activate dense and mixed areas in places beyond the areas adjacent to the railway station should be considered.…”
Section: Criterion Based On Travel Modementioning
confidence: 99%
“…Accordingly, Kaufman et al [33] found in his studies that car use was mainly explained by the local and sub-regional built environment (e.g., walkability, access to work by bus) rather than rail access and Efforts to activate dense and mixed areas in places beyond the areas adjacent to the railway station should be considered.…”
Section: Criterion Based On Travel Modementioning
confidence: 99%